2023
DOI: 10.1002/fft2.200
|View full text |Cite
|
Sign up to set email alerts
|

An alternative source of probiotics: Water kefir

Abstract: The aim of this review was to compile the origin and distribution of water kefir, its production, microbial diversity, fermentation dynamics, health effects, and its place in national/international food legislation. Water kefir is a traditional, slightly carbonated fermented beverage with a lactic acid content of up to 2%. It is obtained by fermenting sugar by kefir grains, which are white or yellowish in color and translucent in appearance. The types of microorganisms in the water kefir differ depending on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…6 Researchers have also found that dairy products fermented by kefir have anti-cancer, antibacterial, anti-allergic, anti-diabetic, anti-inflammatory, antioxidant, and anti-hypertensive effects. 7,8 Additionally, kefir could improve the intestinal tract and digestive system and reduce lactose intolerance. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Researchers have also found that dairy products fermented by kefir have anti-cancer, antibacterial, anti-allergic, anti-diabetic, anti-inflammatory, antioxidant, and anti-hypertensive effects. 7,8 Additionally, kefir could improve the intestinal tract and digestive system and reduce lactose intolerance. 9…”
Section: Introductionmentioning
confidence: 99%
“…6 Researchers have also found that dairy products fermented by kefir have anti-cancer, antibacterial, anti-allergic, anti-diabetic, anti-inflammatory, antioxidant, and anti-hypertensive effects. 7,8 Additionally, kefir could improve the intestinal tract and digestive system and reduce lactose intolerance. 9 Kefir grains exhibit an irregular morphology, characterized by surface undulations, irregularities, or pronounced distortion, and possess a certain degree of elasticity and acidity.…”
Section: Introductionmentioning
confidence: 99%
“…Water kefir is produced by fermenting a carbohydrate‐containing solution with water kefir grains (WKG) at 21–25°C for 48–96 h (Pendón et al., 2022 ). Various substrates could be used to obtain WK beverages, such as apple, mandarin, persimmon, quince, grape, kiwi, coconut, sugarcane juice, honey, grape molasses, ginger, and onion (Cufaoglu & Erdinc, 2023 ; Güzel‐Seydim et al., 2023 ; Lynch et al., 2021 ; Moretti et al., 2022 ; Pendón et al., 2022 ). In addition to the fermentation environment, various fermentation parameters related to WK production have been studied (Gökırmaklı et al., 2023 ; Laureys et al., 2018 , 2019 , 2021 ; Laureys & De Vuyst, 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the microorganism groups in WKG exhibited probiotic properties (Angelescu et al., 2019 ; Koh et al., 2018 ; Romero‐Luna et al., 2019 , 2020 ). Previous studies have investigated the health impacts of consuming WK (Cufaoglu & Erdinc, 2023 ; Moretti et al., 2022 ). Several studies have shown that consumption of WK may have potentially favorable effects against irritable bowel syndrome (Gökırmaklı et al., 2023 ) and has gastro‐protective (Brasil et al., 2019 ), cholesterol‐lowering (Rocha‐Gomes et al., 2018 ), antidiabetic and antihyperlipidemic (Alsayadi et al., 2014 ), antimicrobial (Gonda et al., 2019 ), anti‐inflammatory (Hsieh et al., 2012 ), antioxidant (Alsayadi et al., 2013 ), and hepato‐protective properties.…”
Section: Introductionmentioning
confidence: 99%
“…When these microorganisms are introduced to coconut water, they initiate a transformation that not only preserves the natural goodness of coconut water but also enhances its nutritional profile. These grains are used to ferment sugarwater mixtures and are now collectively referred to as "water kefir grains" or "sugary kefir grains" [8], the main microorganisms in the water kefir grain are lactic acid bacteria, yeast, and acetic acid bacteria. The broad usage of water kefir for preventing IBD (inflammatory bowel disease) [9], improving intestinal permeability [10], and reducing constipation and diarrhea [11] were mentioned in other articles.…”
Section: Introductionmentioning
confidence: 99%